Repositório institucional a serviço da Ciência, Tecnologia e Sociedade: uma análise sobre o RiUFF e LUME - Bazilio, Ana Paula Matos (Universidade Federal de São Carlos, 2022)
In this research, the role of repositories is highlighted as an important tool at the service of Science, Technology and Society, thus streamlining the process of scientific communication and open access. It is necessary that scientists and researchers recognize the importance of these for the dissemination of the results of their research to their peers and to society. The present work has, as a general objective, to analyze the national and international scientific production on the subject institutional repository and to describe the Institutional Repository of the Federal Fluminense University (RiUFF) and the Digital Repository of the Federal University of Rio Grande do SUL (LUME). The research unfolds in the following specific objectives: to identify the main types of existing repositories in the scientific literature; investigate the main challenges for the development of repositories and for open access and relate the issue of institutional repositories within the scope of Brazilian federal universities. Methodologically, the research is configured as quantitative and qualitative with descriptive exploratory approaches. First, a document review was carried out on the following websites and directories: OpenDoar, Ranking Web of Repositories, ROARMAP, Portal e-MEC, OASIS.BR, websites of Brazilian federal universities, RiUFF and LUME. Afterwards, a literature review was carried out in the databases: RCAAP, BDTD, SCOPUS, Web of Science, SCIELO, REDALYC and BENANCIB. In a second moment, a case study was carried out, in the Institutional Repository of UFF (RiUFF) and in the Digital Repository of the Federal University of Rio Grande do Sul (LUME). In order to analyze the RiUFF, the experience report method was adopted. In the results, the types of repositories were systematized, such as: digital, institutional, scientific, research data, preprints and learning objects. With the quantitative research in national and international bases and directories, through the results it was possible to identify that the scientific production on IR is predominant in the English language and that countries with a high economic and social level have a greater number of repositories. In quantitative research on the WEB OF SCIENCE, SCIELO and REDALYC, it appears that the area of knowledge that was most concerned with studying the repository theme was Information Science. In 2020 and 2021, with the COVID-19 pandemic, there is an increase in the scientific literature in articles in the databases. There is also an increase in repository initiatives in the pandemic context, in order to accelerate the process of communicating and disseminating Science. Through research on the institutional sites of Brazilian federal universities, it appears that 85% of them have repositories, which demonstrates a concern on the part of librarians, information professionals and researchers with the socialization of scientific knowledge. Regarding the literature on the subject of repository, it appears that universities and research institutions need more studies on the subject and a better systematization of the concepts of different types of repository in the scientific literature. Through the case study, it is identified that the institutional repository (RiUFF) needs better dissemination to the entire academic community and society in general. It appears that LUME is a successful initiative due to the institution's organizational culture
Institutional repository at the service of Science, Technology and Society: an analysis of RiUFF and LUME
Keywords: Repositório institucionais; Comunicação cientifica; Acesso aberto; Institutional repository; Open Access; Scientific communication; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO; CIENCIAS SOCIAIS APLICADAS